LET'S TALK ABOUT SAFETY—CAN INJURY PREVENTION DO MORE HARM THAN GOOD?. (7th October 2012) - Roberts, I
Abstract : Walking and cycling can be pleasant and healthy and by replacing car use can reduce greenhouse gas emissions. Many people say that they would walk and cycle if it was not so dangerous. However, we are much less aware than we should be of the risks of not walking and cycling. Physical inactivity substantially increases our risk of heart disease, stroke and cancer. The overall risk of death for adults who cycle to work on a regular basis is between 10% and 30% lower than for those who drive to work. This benefit persists after controlling for a range of factors that might differ between cyclists and motorists. Cycling may appear dangerous but not cycling is more dangerous. Public health advocates should shift their focus from injury reduction to safety promotion. There should also be greater emphasis on improving trauma care, particularly given the recent evidence that tranexamic acid safely reduces mortality in bleeding trauma patients. Indeed, injury advocates should endeavour to ensure universal access to this inexpensive life saving treatment.